What Causes Future Gold Price Volatility in Indonesia? - Cynthia Sari Dewi (PT FORMOSA CENDEKIA GLOBAL, 2022)
The purpose of this study is to determine the factors that influence the future volatility of gold commodities in Indonesia. Methods of quantitative research as well as secondary data are utilized in this study. The years 2011 to 2018 are used in this study example. On the official website, there is a total of 32 data collected quarterly. SPSS version 24 is the software that is being utilized. The findings, the exchange rate is the only factor that has impact on future gold commodities. Other factors, including as the consumer price index and the stock market index, have no such impact. Research can be used to determine the reasons of price volatility from macroeconomic influences on future gold commodities